PENGARUH UPAH MINUMUM TERHADAP TENAGA KERJA DI NEGARA DENGAN TINGKAT PENGHASILAN RATA-RATA YANG RENDAH - Veny Anindya Puspitasari (Universitas Bunda Mulia, 2017)
The minimum wage is a macroeconomic issue that is still debated, Basically, the minimum wage policy aimed to protect workers, so that thet earn an adequate wages to finance the basic needs of their life. Practically, the minimum wage policy often encounters its purpose because it is regarged as miserable for those who have no expertise. This phenomenon is mainly happening in the low –avegrage- income countries that have many unskilled workers. Gahana, Indonesia, Costra Rica were used to be analyzed in this paper. According to International Water Association data year 2006, those countris earn income per capita less than US 9,200 and were categorized as low average – income countries. This research found that minimum wage impelentation in all three countries was not effective. When minimum wage policy was implemented, a lot of people felt aggrieved.Keywords : Economic polict, Minimum wage, Income